Enseñanza del orden y la seguridad para la prevención de accidentes en los estudiantes de la Unidad Educativa Homero Castro Zurita, Naranjal, Provincia del Guayas - Romero Calle, Darwin Fredy (2020)
This research work was carried out with the objective of determining the importance in the teaching of order and safety, through the application of methods and techniques for accident prevention, in high school students of the Homero Castro Zurita Educational Unit. The field research allowed to know the needs presented in the electromechanical workshops in the field of safety, this motivated the development and implementation of a safety manual, which should be used during the practices in the electromechanical workshop, where the importance is detailed of the application of safety methods and techniques for accident prevention. The accident risks that occur during the practical classes in the workshop will be reduced, through the application of the safety manual considered an important tool for teachers and students, who hope to apply the order as a safety technique for personal health care , accident prevention, promote and foster a culture of prevention.